2020
DOI: 10.1002/aoc.5928
|View full text |Cite
|
Sign up to set email alerts
|

Cu2O/reduced graphene oxide/TiO2nanomaterial: An effective photocatalyst for azide‐alkyne cycloaddition with benzyl halides or epoxide derivatives under visible light irradiation

Abstract: Cu 2 O/reduced graphene oxide/TiO 2 (Cu 2 O/rGO/TiO 2) photocatalyst was synthesized under ultrasonic irradiation. The nanomaterial was identified by scanning electron microscopy (SEM), transmission electron microscopy (TEM), Xray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), Fourier transform infrared (FT-IR) spectroscopy, UV-vis absorption, and inductively coupled plasma optical emission spectroscopy (ICP-OES). The Cu 2 O/rGO/TiO 2 photocatalyst was utilized in "click" reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…More complex, multicomponent materials based on copper oxide and graphene oxide were also investigated, for example, Jang et al reported delafossite CuFeO 2 /NiFe/reduced graphene oxide photoelectrocatalyst with high photoactivity of −2.4 mA cm −2 at 0.4 V RHE in NaOH electrolyte [ 149 ]. The Cu 2 O/reduced graphene oxide/TiO 2 (Cu 2 O/rGO/TiO 2 ) photocatalyst synthesized under ultrasonic irradiation was studied in “click” reaction for the synthesis of 1,2,3-triazoles via one pot multicomponent reaction of benzyl halide or epoxide derivatives with alkynes under visible light irradiation [ 209 ].…”
Section: Copper Oxide Based Materialsmentioning
confidence: 99%
“…More complex, multicomponent materials based on copper oxide and graphene oxide were also investigated, for example, Jang et al reported delafossite CuFeO 2 /NiFe/reduced graphene oxide photoelectrocatalyst with high photoactivity of −2.4 mA cm −2 at 0.4 V RHE in NaOH electrolyte [ 149 ]. The Cu 2 O/reduced graphene oxide/TiO 2 (Cu 2 O/rGO/TiO 2 ) photocatalyst synthesized under ultrasonic irradiation was studied in “click” reaction for the synthesis of 1,2,3-triazoles via one pot multicomponent reaction of benzyl halide or epoxide derivatives with alkynes under visible light irradiation [ 209 ].…”
Section: Copper Oxide Based Materialsmentioning
confidence: 99%
“…According to the results of elemental survey in Figure 7a, peaks at the binding energies of 103.08 eV (Si2p), 285.08 (C1s), 395.28 (N1s), 533.32 (O1s), 725.27 (Fe2p), and 932.90 (Cu2p) affirmed the presence of Fe, O, Si, N, C, and Cu in the structure of the nano Fe 3 O 4 ‐SiO 2 @Glu‐Cu(II). [ 30,37 ] The XPS analysis of Cu2P (Figure 7b) represented that copper ions presented as Cu (II). The bands at binding energies of 934.58 and 940.28–944.18 eV (as shake‐up satellite peaks) attributed to Cu II 2p3/2 and the peak at 954.38 eV related to Cu II 2p1/2.…”
Section: Resultsmentioning
confidence: 99%
“…Even in 2013, Runo and co-workers performed this reaction in solvent-free conditions with a ball-milling system 38 . Cu 2 O/reduced graphene oxide/TiO 2 (Cu 2 O/rGO/TiO 2 ) photocatalyst under ultrasonic irradiation was also used to synthesize these compounds with epoxide derivatives and alkynes 39 . Although many ways to synthesize alkyl azides have been reported in various research groups, methods for making aryl azides are limited 40 .…”
Section: Introductionmentioning
confidence: 99%